Unveiling the precipitation behavior and mechanical properties of Co-free Ni47-xFe30Cr12Mn8AlxTi3 high-entropy alloys. (10th August 2022) - Fan, Jiantao; Fu, Liming; Sun, Yanle; Xu, Feng; Ding, Yi; Wen, Mao; Shan, Aidang
Highlights: Effects of Al on precipitation behavior and mechanical properties of Co-free Ni47- x Fe30 Cr12 Mn8 Al x Ti3 ( x = 3, 5, and 7 at.%) HEAs were studied. Al as a BCC stabilizer in the current alloy system inhibits the formation of η phase while improves the formation of B2-ordered phase. The precipitation behavior of L12 precipitates is enhanced due to the decreased FCC/L12 lattice mismatch with increasing Al content. The Ni42 Fe30 Cr12 Mn8 Al5 Ti3 HEA shows a better combination of a yield strength of 661 MPa and tensile ductility of 29.7%. This work provides references foundation for the optimization design on compositions of precipitated Co-free HEAs with excellent performance. Abstract: Precipitate hardening is considered as an effective method to strengthen High- and medium-entropy alloys (HEAs and MEAs), especially the recently developed Co-free HEAs/MEAs. In this work, a systematic study on precipitation and mechanical behaviors of a Co-free HEAs with dilute amount of Al addition, Ni47- x Fe30 Cr12 Mn8 Al x Ti3 ( x = 2 at.%, 5 at.% and 7 at.%), is presented. Results shown that the Ni45 Fe30 Cr12 Mn8 Al2 Ti3 has a face-centered cubic (FCC) + L12 + η three-phased structure. With increasing Al content, the formation of η phase is inhibited, accompanying with an enhanced formation of B2 phase, and FCC + L12 + B2 three-phased structure is thus observed in alloys with x = 5 and 7. The constrained lattice mismatch between FCC matrix and L12 precipitates is decreased with increasing Al content, leading to an enhanced precipitation behavior of L12 phase. As a result of microstructural evolution, the mechanical properties of the aged HEAs changed: the Ni42 Fe30 Cr12 Mn8 Al5 Ti3 alloy exhibits a better combination of a yield strength of 661 MPa and tensile ductility of 29.7% as compared to the 2 at.% Al alloyed HEA; and addition of Al beyond 5 at.% results in an increase of strength with a large expense of ductility. We believe that the present work is helpful for developing high-performance Co-free HEAs/MEAs strengthened by nanoprecipitates via composition optimizing.